A 2 year histopathological audit for non-oncological hysterectomies in a tertiary care hospital - Bhat, Salma; Bhat, Nazia; Niyaz, Isma; Wani, Rohi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the most common gynecological surgery in the world and is considered to be the most definitive treatment option for various diseases like DUB (dysfunctional uterine bleeding), leiomyoma, adenomyosis, chronic pelvic pain, prolapse, and malignancy. The aim of the study was to evaluate the surgical indications, routes of surgery and the correlation between preoperative diagnosis and histopathological examination of hysterectomy specimens Methods: This was a retrospective audit. The pre-operative diagnosis and histopathologic data of all consecutive specimens of hysterectomies were collected and analysed. Those with confirmed malignancy before operation were excluded. All elective as well as emergency hysterectomies (including obstetric hysterectomies) were analyzed. Preoperative indications were compared with the final histopathological report. Results: Most common indication for hysterectomy was symptomatic fibroid uterus followed by utero-vaginal prolapse and obstetric causes. Overall, there was no pathology identified in approximately 50% of all hysterectomies received in our department. Conclusions: Proper audit and review can help in improving the quality of health care in our country. The results of our study may help to reduce inappropriate indications for hysterectomy.